DHFR-mediated effects of methotrexate in medulloblastoma and osteosarcoma cells: the same outcome of treatment with different doses in sensitive cell lines - Neradil, Jakub; Pavlasova, Gabriela; Sramek, Martin; Kyr, Michal; Veselska, Renata; Sterba, Jaroslav (Oncology reports, 2015)
Although methotrexate (MTX) is the most well-known antifolate included in many standard therapeutic regimens, substantial toxicity limits its wider use, particularly in pediatric oncology. Our study focused on a detailed analysis of MTX effects in cell lines derived from two types of pediatric solid tumors: medulloblastoma and osteosarcoma. The main aim of this study was to analyze the effects of treatment with MTX at concentrations comparable to MTX plasma levels in patients treated with high-dose or low-dose MTX. The results showed that treatment with MTX significantly decreased proliferation activity, inhibited the cell cycle at S-phase and induced apoptosis in Daoy and Saos-2 reference cell lines, which were found to be MTX-sensitive. Furthermore, no difference in these effects was observed following treatment with various doses of MTX ranging from 1 to 40 µM. These findings suggest the possibility of achieving the same outcome with the application of low-dose MTX, an extremely important result, particularly for clinical practice. Another important aspect of treatment with high-dose MTX in clinical practice is the administration of leucovorin (LV) as an antidote to reduce MTX toxicity in normal cells. For this reason, the combined application of MTX and LV was also included in our experiments; however, this application of MTX together with LV did not elicit any detectable effect. The expression analysis of genes involved in the mechanisms of resistance to MTX was a final component of our study, and the results helped us to elucidate the mechanisms of the various responses to MTX among the cell lines included in our study.
Keywords: Cerebellar Neoplasms; Reverse Transcriptase Polymerase Chain Reaction; osteosarkom; Cell Proliferation; meduloblastom; Humans; nádorové buněčné linie; chemorezistence; Folic Acid Antagonists; Methotrexate; Bone Neoplasms; methotrexát; Medulloblastoma; antagonisté kyseliny listové; Flow Cytometry; nádory kostí; proliferace buněk; dihydrofolátreduktasa; polymerázová řetězová reakce s reverzní transkripcí; Drug Resistance, Neoplasm; Osteosarcoma; průtoková cytometrie; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Tetrahydrofolate Dehydrogenase; lidé; nádory mozečku; Cell Line, Tumor